2015
DOI: 10.1073/pnas.1507514112
|View full text |Cite
|
Sign up to set email alerts
|

Maternal testosterone exposure increases anxiety-like behavior and impacts the limbic system in the offspring

Abstract: During pregnancy, women with polycystic ovary syndrome (PCOS) display high circulating androgen levels that may affect the fetus and increase the risk of mood disorders in offspring. This study investigated whether maternal androgen excess causes anxiety-like behavior in offspring mimicking anxiety disorders in PCOS. The PCOS phenotype was induced in rats following prenatal androgen (PNA) exposure. PNA offspring displayed anxiety-like behavior in the elevated plus maze, which was reversed by flutamide [androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 41 publications
10
83
1
Order By: Relevance
“…The relationship between PCOS and mental health is not yet clear but may be independent of a strict diagnosis of infertility. Ongoing research has suggested that testosterone levels may play a role in brain development, which could provide a possible explanation for this association [41]. Health care providers who care for women with infertility or PCOS should be aware that their patients may face challenges either at time of consultation for infertility or in the future related to anxiety, depression, and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PCOS and mental health is not yet clear but may be independent of a strict diagnosis of infertility. Ongoing research has suggested that testosterone levels may play a role in brain development, which could provide a possible explanation for this association [41]. Health care providers who care for women with infertility or PCOS should be aware that their patients may face challenges either at time of consultation for infertility or in the future related to anxiety, depression, and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is not clear how effectively candidate hormones such as cortisol or noradrenaline cross the placental barrier. This question is also being investigated in animal studies, and there is evidence that maternal exposure to testosterone during pregnancy can impact the limbic system of offspring in rats, and contribute to elevated anxiety-like behavior (Hu et al 2015). It is also unclear to what extent changes in fetal blood flow, related to maternal anxiety, actually explain psychological outcomes in the babies.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Support for AR-mediated androgen actions influencing the progression of PCOS includes that variation in androgen sensitivity via the CAG triplet repeat length polymorphism of the AR (11) is associated with PCOS prevalence (12), and alternative splicing of the AR in granulosa cells is associated with aberrant follicle development (13,14). Treatment with the AR antagonist flutamide is reported to restore ovulation in some women with PCOS (15) and rescue acyclicity (16) and anxiety-like behavior (17) in PCOS mouse models. Moreover, we recently identified that loss of AR signaling protects female mice from induction of PCOS features by prenatal hyperandrogenism (18).…”
mentioning
confidence: 99%